Evaluation of Immersion in the Flow State from the Variation of the Instagram Web Interface - Marques, Alice Cabral de Avelar; Marques-Neto, Humberto Torres (Journal on Interactive Systems, 2026)
Background: Social media interfaces employ design strategies that encourage continuous engagement, which may influence users’ immersion and flow state. Investigating how interface design elements contributes to inducing a flow state in users is essential to promote ethical and mindful design practices. Purpose: This study aims to explore the impact of Instagram’s interface design on user behavior, with a particular focus on indications of the flow state. Methods: We developed a browser extension based on the Hook model to carry out interventions in the interface, aiming to remove triggers, reduce rewards, and limit user actions. A case study was conducted with undergraduate students who navigated both the modified and standard Instagram web interfaces. The Online Flow Questionnaire was used to measure flow state levels and, additionally, participants who used the extension took part in a brief interview to gather qualitative insights about their experience. Results: Findings indicate a subtle variation in the flow state between the modified and standard interfaces, suggesting that interface changes influence user’s flow state. Results also suggest that the device type can modulate the flow state and that individual factors, such as technological familiarity, can influence user interaction. Conclusion: Interface design elements encourage users to remain engaged for longer periods, providing an initial indication of the impact of design on user flow state. The findings reinforce the need for ethical design approaches that balance user retention with mental well-being.